Evaluation of capsicum (Capsicum annuum L.) genotypes for variety improvement - Bhattarai, D. R.; Maharjan, S. K.; Gautam, I. P.; Subedi, S.; Pokhrel, S. (Journal of Agriculture and Forestry University, 2020)
An experiment was done at Horticulture Research Division, Nepal Agricultural Research Council (NARC), Khumaltar, Nepal under polyhouse condition to access different traits of six capsicum genotypes: HRDCAP-001, HRDCAP-003, HRDCAP-004, HRDCAP-005, HRDCAP-006, and California Wonder (check variety) with the objective to evaluate yield and quality. The experiment was done by using Randomized Complete Block Design (RCBD) with four replications for each treatment. All the collected data were analyzed by using Gentstat statistical software package. Results revealed that tested genotypes were significantly different (p